Evaluation of potential for peak demand reduction of residential buildings by household appliances with demand response. Issue 4 (17th October 2022) - Ono, Tetsushi; Hagishima, Aya; Tanimoto, Jun
Abstract: Residential appliances remotely controlled by IoT for demand response has attracted much attention for effective peak demand reduction of the uncertainty of consumers' behaviors. To promote the technology development of such appliances, estimation of the potential for peak demand reduction according to the type of appliances is strongly needed. With this background, the authors conducted a data analysis of demand curves of not only the entire household but also the branches acquired at 496 dwellings in Osaka. Based on this analysis, the potential of peak reduction of aggregated demand of various groups with different dwelling size were quantified for major five appliances, namely air conditioners, microwave ovens, refrigerators, washing machines, and dish washers.